2022
DOI: 10.1080/20961790.2022.2031548
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Outcomes in Nonfatal Road Traffic Accidents: A Portuguese Medico-Legal Approach

Abstract: The objective of this study was to compare the outcomes of nonfatal road traffic accidents by the victims’ age group and sex. We used the Portuguese medico-legal rules for personal injury assessment, in the scope of the Civil Law in that country, which includes a three-dimensional methodology. This was a retrospective study including 667 victims of road traffic accidents aged 3–94 years old. Their final medico-legal reports all used the Portuguese methodology for personal injury assessment. Outcomes were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
2
5
1
Order By: Relevance
“…However, despite an absence of a significant OR, we noticed a tendency towards more days of Total Temporary Functional Deficit in the older population, in agreement with other authors [ 18 , 28 ] and as we found in our previous study without matching ISS samples ( p = 0.001) [ 25 ]. Nevertheless, we should note that seniors are more vulnerable to bed rest and reduced food intake, which should be avoided due to the effects of immobilisation (loss of strength and muscle mass, decrease in aerobic capacity, and functional decline); such effects already appear with just ten days of bed rest [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, despite an absence of a significant OR, we noticed a tendency towards more days of Total Temporary Functional Deficit in the older population, in agreement with other authors [ 18 , 28 ] and as we found in our previous study without matching ISS samples ( p = 0.001) [ 25 ]. Nevertheless, we should note that seniors are more vulnerable to bed rest and reduced food intake, which should be avoided due to the effects of immobilisation (loss of strength and muscle mass, decrease in aerobic capacity, and functional decline); such effects already appear with just ten days of bed rest [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…A significant difference was found for Partial Temporary Functional Deficit , with a higher OR in G2. This result was also found in a previous study ( p = 0.005) [ 25 ] and may be related to the more demanding physical rehabilitation period in younger people, given the greater need for their activity ( Table 2 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations